# Trig

posted by .

Verify that (secx/sinx)*(cotx/cscx)=cscx is an identity.

(x=theta BTW)

• Trig -

(secx/sinx)*(cotx/cscx)
= (secx/cscx)(cotx/sinx)
= (sinx/cosx)*cotx*(1/sinx)

The last steps should be obvious

## Similar Questions

1. ### Math

Verify the identity . (cscX-cotX)^2=1-cosX/1+cosX _______ sorry i cant help you (cscX-cotX)=1/sinX - cosX/sinX = (1-cosX)/sinX If you square this you have (1-cosX)^2/(sinX)^2 Now use (sinX)^2 = 1 - (cosX)^2 to get (1-cosX)^2 / 1 - …
2. ### calculus

express in sinx 1 1 ---------- + -------- cscx + cotx cscx - cotx and express in cosx 1 + cot x ------- - sin^2x cscx = 1/sinx so what do i do w. that extra one on the top!?
3. ### trig

express this in sinx (1/ cscx + cotx )+ (1/cscx- cotx) i got 2sinx is that right?
4. ### drwls

My previous question: Verify that (secx/sinx)*(cotx/cscx)=cscx is an identity. (secx/sinx)*(cotx/cscx) = (secx/cscx)(cotx/sinx) = (sinx/cosx)*cotx*(1/sinx) "The last steps should be obvious" Not to me. I can convert (sinx/cosx) to …
5. ### Pre-Calculus

Find a numerical value of one trigonometric function of x if tanx/cotx - secx/cosx = 2/cscx a) cscx=1 b) sinx=-1/2 c)cscx=-1 d)sinx=1/2
6. ### Trig

verify the following identity: tanx+cotx/cscx=secx